Bovine herpesvirus-5 infection in a rabbit experimental model: Immunohistochemical study of the cellular response in the CNS - Machado, Gisele Fabrino [UNESP]; Bernardi, Fernanda; Hosomi, Fernando Y.M.; Peiró, Juliana Regina [UNESP]; Weiblen, Rudi; Roehe, Paulo M.; Alessi, Antonio C. [UNESP]; Melo, Guilherme D. [UNESP]; Ramos, Adriano T.; Maiorka, Paulo C. (Elsevier, 2013)
Since little information is available regarding cellular antigen mapping and the involvement of non-neuronal cells in the pathogenesis of bovine herpesvirus type 5 (BHV-5) infection, it were determined the BHV-5 distribution, the astrocytic reactivity, the involvement of lymphocytes and the presence of matrix metalloproteinase (MMP)-9 in the brain of rabbits experimentally infected with BHV-5. Twelve New Zealand rabbits that were seronegative for BHV-5 were used for virus inoculation, and five rabbits were used as mock-infected controls. The rabbits were kept in separate areas and were inoculated intranasally with 500 μl of virus suspension (EVI 88 Brazilian isolate) into each nostril (virus titer, 107.5 TCID50). Control rabbits were inoculated with the same volume of minimum essential medium. Five days before virus inoculation, the rabbits were submitted to daily administration of dexamethasone. After virus inoculation, the rabbits were monitored clinically on a daily basis. Seven rabbits showed respiratory symptoms and four animals exhibited neurological symptoms. Tissue sections were collected for histological examination and immunohistochemistry to examine BHV-5 antigens, astrocytes, T and B lymphocytes and MMP-9. By means of immunohistochemical and PCR methods, BHV-5 was detected in the entire brain of the animals which presented with neurological symptoms, especially in the trigeminal ganglion and cerebral cortices. Furthermore, BHV-5 antigens were detected in neurons and/or other non-neural cells. In addition to the neurons, most infiltrating CD3 T lymphocytes observed in these areas were positive for MMP-9 and also for BHV-5 antigen. These infected cells might contribute to the spread of the virus to the rabbit brain along the trigeminal ganglia and olfactory nerve pathways. © 2013 Elsevier Ltd.
Keywords: Animal model; Astrocytes; Inflammation; Lymphocytes; Matrix metalloproteinases; Bovine herpespirus 5 antigen; cell antigen; dexamethasone; gelatinase B; unclassified drug; virus antigen; animal cell; animal experiment; animal model; animal tissue; antibody titer; astrocyte; B lymphocyte; Bovine herpes virus; brain; brain cortex; CD3+ T lymphocyte; cellular immunity; central nervous system; controlled study; enzyme activity; experimental model; herpes virus infection; immunohistochemistry; immunopathogenesis; inoculation; lymphocyte; lymphocytic infiltration; male; nerve cell; neurologic disease; nonhuman; nose; priority journal; rabbit; respiratory tract disease; suspension cell culture; symptomatology; T lymphocyte; trigeminus ganglion; Animals; Brain; Cattle; Disease Models, Animal; Encephalitis, Viral; Herpesviridae Infections; Herpesvirus 5, Bovine; Male; Matrix Metalloproteinase 9; Meningoencephalitis; Rabbits